Making Sense of the Sustainable Smart PSS Value Proposition - Lugmair, Nina; Ries, Lena; Schymanietz, Martin; Beckmann, Markus; Roth, Angela (ICIS 2022 Proceedings.3., 2022)
While academia attributes superior value potential to sustainable smart PSS (SSPSS), in practice, they are not widely implemented. To address this gap, we analyze how the notion of SSPSS value is constructed through sensemaking. Adopting a case study approach, we explore differences in organizational sensemaking. Moreover, we analyze how the three functional roles “digital innovation and technology”, “sustainability”, and “market” involved in innovating SSPSS make sense of the value proposition. We conclude that value is subjective and the value proposition of SSPSS is multi-faceted. Each facet is constructed through the interaction of organizational, functional roles’, and individual sensemaking. At the organizational level, commitment, identity, and expectations influence the creation of shared meaning. At the functional role level, actors differ in their sensemaking based on the cognitive frames applied. At the individual level, subjective beliefs impact sensemaking. Hence, sensemaking is a multi-level process that raises the question of alignment.<br